Diversité Variétale, Qualité Et Utilisation Du Maïs (Zea Mays) En Afrique De l’Ouest : Revue Critique - Semassa, A. J.; Padonou, S.W.; Anihouvi, V.B.; Akissoé, N.H.; Adjanohoun, A.; Baba-Moussa, L. (European Scientific Journal, ESJ, 2016)
Maize (Zea mays) is a cereal cultivated through all the region of the world. Its constitutes one of the cereals the most used for human consumption. The current review focused on the diversity, the nutritional quality and the forms of use of maize in West Africa region. The review allowed to notice that more than twenty varieties of maize were cultivated in Bénin and in the sub-region. With regard to nutritional aspect, those different varieties of maize contained variable amounts of starch (64-78%), fat (4- 6%), protein (7-12%), crude fibers (2-2.5%), ash (1-1.5%) and sugar (1-3%). Potassium (324.8-344 mg /100g), magnesium (107.9-115 mg/100g) and phosphorus (99,6-276 mg/100g) were the main mineral in maize. Likewise, leucine, isoleucine, tryptophane and valine all contained in the germ were the main amino acids in maize. These chemical components can be alone or in a possible synergy of action responsible for numerous technological advantages of maize. Through its chemical and technological characteristics the maize constitutes an important raw material for many culinary recipes in West Africa region. So it is important to make the inventory of the main varieties cultivated in the sub-region, to compare them at both nutritional and technological aspects for prospective actions to undertake in order to improve the yield of these varieties and to guarantee food security for the populations.